Fluid mechanics: With problems and solutions, and an aerodynamic laboratory - Krause, Egon (Springer, 2014)
This textbook introduces the major branches of fluid mechanics of incompressible and compressible media, the basic laws governing their flow, and gas dynamics. Fluid Mechanics demonstrates how flows can be classified and how specific engineering problems can be identified, formulated and solved, using the methods of applied mathematics. The material is elaborated in special applications sections by more than 200 exercises and separately listed solutions. The final section comprises the Aerodynamics Laboratory, an introduction to experimental methods treating eleven flow experiments. This class-tested textbook offers a combination of introduction to the major fundamentals, many exercises, and a detailed description of experiments.